Tomoscopy: Time‐Resolved Tomography for Dynamic Processes in Materials. Issue 45 (23rd September 2021) - García‐Moreno, Francisco; Kamm, Paul Hans; Neu, Tillmann Robert; Bülk, Felix; Noack, Mike Andreas; Wegener, Mareike; von der Eltz, Nadine; Schlepütz, Christian Matthias; Stampanoni, Marco; Banhart, John
Abstract: The structure and constitution of opaque materials can be studied with X‐ray imaging methods such as 3D tomography. To observe the dynamic evolution of their structure and the distribution of constituents, for example, during processing, heating, mechanical loading, etc., 3D imaging has to be fast enough. In this paper, the recent developments of time‐resolved X‐ray tomography that have led to what one now calls "tomoscopy" are briefly reviewed A novel setup is presented and applied that pushes temporal resolution down to just 1 ms, that is, 1000 tomograms per second (tps) are acquired, while maintaining spatial resolutions of micrometers and running experiments for minutes without interruption. Applications recorded at different acquisition rates ranging from 50 to 1000 tps are presented. The authors observe and quantify the immiscible hypermonotectic reaction of AlBi10 (in wt%) alloy and dendrite evolution in AlGe10 (in wt%) casting alloy during fast solidification. The combustion process and the evolution of the constituents are analyzed in a burning sparkler. Finally, the authors follow the structure and density of two metal foams over a long period of time and derive details of bubble formation and bubble ageing including quantitative analyses of bubble parameters with millisecond temporal resolution. Abstract : Recent developments of time‐resolved X‐ray tomography, called "tomoscopy, " are presented. Tomoscopy provides up to 1000 tomograms per second at µm‐range resolution, running experiments for minutes without interruption. Tomoscopy is applied to study various dynamic processes in materials science.